Livestock grazing systems and sustainable development in the Mediterranean and Tropical areas Recent knowledge on their strengths and weaknesses - Moulin, Charles-Henri; Ickowicz, Alexandre (éditions Quae, 2023)
Family-run ruminant grazing systems in the Mediterranean and tropical areas contribute directly to eight of the seventeen Sustainable Development Goals (SDGs) of the United Nations 2030 Agenda. For a long time, these livestock systems have been on the fringe of agricultural investment efforts. However, they have undeniable assets to meet these SDGs in interaction with other forms of livestock production systems present in the territories. But they also face a set of constraints that call into question their continuity. The interdisciplinary synthesis presented here aims to answer three key questions: How can the adaptive capacities of these grazing livestock systems be strengthened to respond to climatic, social and economic changes? How to improve their efficiency at different levels of organisation and on social, economic and environmental levels? Finally, how can these livestock systems contribute to innovation processes for the agro-ecological transition? This book is based on recently published research by UMR Selmet (CIRAD-INRAE-Institut Agro) on a variety of sites around the world and in a broad international partnership. It is intended for the teaching and scientific community, students, and stakeholders in the livestock sector and in the territories, who are involved at different decision-making levels.